UPAYA MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA MELALUI MODEL PEMBELAJARAN TAI MATERI LAJU REAKSI - Rossesa, Rossesa; Muharini, Rini; Hadi, Lukman (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract: The main goal of this study was to improve student’s activity and achievement of reaction rate Team Assisted Individualization (TAI) learning model. A two cycles of classroom action research was conducted. A total of 30 science class students of SMAN 1 Jawai participated in this study. Achievement test, observation sheet, and interview guidelines were used to collect data. Data were analyzed qualitatively and quantitatively. Students would be identified to have improvement on visual, and verbal activity and achievement when they obtained score of 75, 25 and 60 respectively. The result showed that students have pass grade point do to the improvements they made. Those improvements were improve on visual activity from 56,6% to 76,6%, verbal activity from 10% to 26,6% and achievement from 23,3% to 83,3% respectively. Those result indicated that the cooperative learning model type TAI give an positive effect toward student learning activity and achievetment.Keywords: Team Assisted Individualization (TAI), reaction rate, activity and learning outcomes.